Discrepancy Analysis of Guidance and Counseling Program Implementation in Madrasah Tsanawiyah - Sulastrini, Sulastrini; Hidayah, Nur; Rahman, Diniy Hidayatur (JURKAM: Jurnal Konseling Andi Matappa, 2024)
This research aims to identify the discrepancies between the standards of guidance and counseling programs and the actual practices in Madrasah Tsanawiyah (MTs). Initial data indicates that most school counselors do not evaluate their services, attributed to a lack of ability, diminished interest in learning evaluation methods, and inadequate training opportunities. This study employs an evaluation method utilizing a discrepancy model and involves school counselors from MTs across the Malang Raya region. Evaluation data is collected through a scale developed based on the professional school counselor evaluation guidelines from the Missouri Department of Elementary and Secondary Education and the Indonesian Association for Guidance and Counseling (ABKIN) ethical code. Subsequently, the data is statistically analyzed. The research finds that the main focus areas of guidance and counseling services in MTs are ranked as 3, 6, 2, 4, 5, and 1, with the highest focus being on point 3, where professional counselors provide responsive services to groups and individuals. Conversely, the lowest point is in focus area 1, where professional counselors provide basic services using their acquired skills. To achieve optimal services, implementing the guidance and counseling program must address all focus areas attentively. Consequently, improvements and developments aligned with the standards are necessary. Counselors also need to pay heed to points related to implementation that deviate from the existing standards, allowing for improvements to enhance service quality. This evaluation is anticipated to enhance the guidance and counseling programs in MTs and positively impact students, facilitating their optimal development.